The Longest day [videorecording] - Annakin, Ken.; Marton, Andrew; Wicki, Bernhard; Williams, Elmo.; Darryl F. Zanuck Production; Twentieth Century Fox. ([S.l.] Twentieth Century Fox, 1962)
The complete story of the D-day landings at Normandy, as seen through the ages of American, French, British and German participants.
Based on the book by Cornelius Ryan.
This film has been modified from its original version.
VHS.
Credits : Screenplay by Cornelius Ryan.
Richard Burton, Paul Anka, John Wayne.
1962 Oscar Awardee for Special Effects and Cinematography.
Keywords: World War -- Campaigns -- Drama. -- 1939-1945 -- France -- Normandy; Feature films; France -- History -- Invasions -- Drama